Pengaruh Penggunaan Aplikasi Quizztooth Games Terhadap Tingkat Pengetahuan Kesehatan Gigi dan Mulut Kader Dokter Kecil - Aldilawati, Sari; Asmah, Nur; Wijaya, Muhammad F.; Biba, Andi T.; Muthmainnah, Sy. Sri (e-GiGi, 2025)
Abstract: Oral health is an important aspect in maintaining individual well-being, especially in school-age children. The application of QuizzTooth game can be used to improve the oral and dental health knowledge of little doctor cadres. This study aimed to determine the effectiveness of Quizztooth Game application on the knowledge about dental and oral health among little doctor cadres. This was a quasi-experimental study with a pre-post test design. Respondents were 50 students of SD Negeri Tamamaung I Makassar, aged 9-11 years. The results showed that before intervention of the application, only 50% of respondents had high level of knowledge about dental and oral health, 44% of students had moderate level, and 6% of students had poor level. After intervention, all respondents had high level of knowledge, with the mean value of knowledge increased from 13.360 to 19.640 (p=0.000). In conclusion, intervention of QuizzTooth game application has a significant effect on improving the knowledge of little doctor cadres about dental and oral health. Keywords: QuizzTooth game; dental and oral health; little doctor cadre Abstrak: Kesehatan gigi dan mulut merupakan aspek penting dalam menjaga kesejahteraan individu, terutama anak usia sekolah. Aplikasi QuizzTooth game dapat digunakan untuk meningkatkan pengetahuan kesehatan gigi dan mulut kader dokter kecil. Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan aplikasi Quizztooth game terhadap pengetahuan kesehatan gigi dan mulut kader dokter kecil. Jenis penelitian ialah quasi experimental dengan pre-post test design. Responden penelitianSD Negeri Tamamaung I Makassar, berusia 9-11 tahun. Hasil penelitian mendapatkan bahwa sebelum intervensi aplikasi, hanya 50% responden yang memiliki tingkat pengetahuan tinggi, sementara 44% berada pada kategori sedang dan 6% rendah. Sesudah intervensi, seluruh responden mencapai tingkat pengetahuan tinggi (100%), dengan peningkatan nilai rerata pengetahuan dari 13,360 menjadi 19,640 (p=0,000). Simpulan penelitian ini ialah intervensi aplikasi QuizzTooth game berpengaruh bermakna dalam meningkatkan pengetahuan kader dokter kecil tentang kesehatan gigi dan mulut. Kata kunci: QuizzTooth game; kesehatan gigi dan mulut; kader dokter kecil